Abroad experience of electronic jurisdiction - Kanyuka, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The paper aims to explain the trends and problems of electronic justice development abroad. Within the research, the tasks include an analysis of the regulatory documents and organizational features of the implementation the certain measures of court digitalization.The main scientific method used in the article's architecture is deductive. In the conditions of the study, a gradual transition is made from the general trends of electronic justice to their features in different countries.The structure of the article is formed in accordance with theoretical and analytical tasks. It also reflects the use of certain methods of scientific research and scientific materials.The theoretical method is used during the study of the regulatory documents and problems of electronic justice implementation abroad. The materials used for the method application include legislative acts, regulations, strategy and scientific literature.In the article, it is analyzed the development and implementation of the electronic justice system in the USA and the use of the PACER and Case Management/Electronic Case Files System (CM/ECF). The National Model Practice Direction For the Use of Technology in Civil Litigation in Canada is studied. The experience of implementing electronic justice in Poland, Australia and China is described.